Effects of Community Service‐Learning on Heritage Language Learners' Attitudes Toward Their Language and Culture. (9th February 2017) - Pascual y Cabo, Diego; Prada, Josh; Lowther Pereira, Kelly
Abstract: This study examined the effects of participation in a community service‐learning experience on Spanish heritage language learners' attitudes toward their heritage language and culture. Quantitative and qualitative data from heritage language learners demonstrated that engagement in community service‐learning activities as part of the Spanish heritage language program afforded students transformative experiences that enhanced the work done within the classroom walls.